CORPORATE GOVERNANCE: STUDY AND IMPACT - Agrawal, Nitish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate governance is the framework of rules, regulation and procedure through which the company is regulated and governed to maintain the balance between the stakeholders and investors of the company. This paper delves into the role of governance practices within the corporate landscape of India and other related jurisdictions. Corporate governance in its present form is a intricate interplay of legal dimensions, ethics, morality and financial efficiency. Corporate Governance is necessary to foster a culture of awareness and openness, transparency and credibility. Different countries follow diversified corporate governance model by stressing the importance of investors etc. In this paper, we examine the evolution of corporate governance over time in India, UK and USA. We also try to draw a comparison between various corporate practices adopted by the corporations around the world followed by its ultimate impact on their success. The aim of this paper is to evaluate a variety of corporate governance techniques based on factors such as Board Constitution, Board Structure, Board Committees, Exploring the roles of Independent Directors and their responsibilities, examining Conflict of Interest issues, and analyzing the Disclosure of Information requirements. In addition, the paper also stresses upon the growing investor focus on environmental, social, and governance (ESG) issues has prompted a departure from the traditional emphasis on shareholder primacy in India and other jurisdiction. Towards the end, the paper attempts to verify whether better and enhanced corporate governance practices lead to increase in performance and goodwill of the companies.